2019
DOI: 10.3390/microorganisms8010036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non-B HIV-1 Subtypes in North Italy and Analysis of Transmission Clusters Based on Sequence Data Analysis

Abstract: HIV-1 diversity is increasing in European countries due to immigration flows, as well as travels and human mobility, leading to the circulation of both new viral subtypes and new recombinant forms, with important implications for public health. We analyzed 710 HIV-1 sequences comprising protease and reverse-transcriptase (PR/RT) coding regions, sampled from 2011 to 2017, from naive patients in Spedali Civili Hospital, Brescia, Italy. Subtyping was performed by using a combination of different tools; the phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
2
4
1
Order By: Relevance
“…However, this finding agrees with the results obtained through transmission cluster analyses, which showed that subtype G heterosexuals ( Pineda-Peña et al, 2019 ) were more frequently inside clusters when compared to subtypes A and B, indicating that transmission is more active in this subgroup. This is in contrast to what other European studies showed, where it was concluded that non-B subtypes are associated with the heterosexual population and are less frequently found in the transmission clusters ( Lorenzin et al, 2019 ; Paraskevis et al, 2019 ; Pimentel et al, 2022 ). Since our study is based on newly diagnosed patients, we believe that our results present a more recent view of the epidemic in the country that could already reflect a successful impact of pre-exposure prophylaxis (PrEP) among the MSM patients, with a slowdown of HIV transmission clusters in this risk group.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this finding agrees with the results obtained through transmission cluster analyses, which showed that subtype G heterosexuals ( Pineda-Peña et al, 2019 ) were more frequently inside clusters when compared to subtypes A and B, indicating that transmission is more active in this subgroup. This is in contrast to what other European studies showed, where it was concluded that non-B subtypes are associated with the heterosexual population and are less frequently found in the transmission clusters ( Lorenzin et al, 2019 ; Paraskevis et al, 2019 ; Pimentel et al, 2022 ). Since our study is based on newly diagnosed patients, we believe that our results present a more recent view of the epidemic in the country that could already reflect a successful impact of pre-exposure prophylaxis (PrEP) among the MSM patients, with a slowdown of HIV transmission clusters in this risk group.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we established a subtype classification algorithm to define rules for 300 (2.3%) individuals having multiple pol sequences from different time points with subtype variations. In previous studies, the subtyping tools REGA [24] and COMET [25] demonstrated concordant classification for 96.5% [38] or 85.6% [9], respectively, mitigating this problem. Despite these limitations, the densely sampled SHCS remains highly representative and provides important insights on the ongoing transmission of non-subtype B genetic forms in Switzerland [19] [19].…”
Section: Discussionmentioning
confidence: 92%
“…Several European countries have reported increased transmission of non-B subtypes in MSM. This increase has been linked to imported infections from countries where these non-B subtypes are predominant, followed by transmission among the local MSM population [9,10,[12][13][14][38][39][40][41]. Overall, the highest temporal increase in non-B forms among MSM was observed for subtype A and CRF02_AG, both of which are commonly found among HETs and are among the most predominant forms (together with subtype C) in Western Europe [7].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our study a large number of new cases were referred from other surveillance sites to the study center for treatment since 2014; therefore, a peak was observed in the cluster growth predictor curve of many clusters in 2014 (orange lines in Figure 4), whereas no corresponding change was observed in the PDR curves (blue lines in Figure 4). R e , the third phylodynamic parameter that is based on sequence diversity, reflects the efficiency with which an infectious agent is transmitted and is frequently used to model infection dynamics (Novitsky et al, 2015;Ragonnet-Cronin et al, 2018;Jovanovic et al, 2019;Lorenzin et al, 2019;Vasylyeva et al, 2019;Vinken et al, 2019;Zai et al, 2020). We found that R e was accurate and reliable.…”
Section: Perspectives and Recommendationsmentioning
confidence: 86%
“…Clusters with ≥ 10 cases and between two and nine cases were defined as large and small/medium clusters, respectively. The definition of a large cluster is similar to that used in previous studies (Hughes et al, 2009;Leigh Brown et al, 2011;Lorenzin et al, 2019;Rhee et al, 2019;Dennis et al, 2020). We evaluated demographic features of the study population including the time of diagnosis, sex, risk group, age, ethnic group, resident city, marital status, education, and occupation.…”
Section: Relationship Between Large Clusters and Othersmentioning
confidence: 99%